Spatial and temporal patterns of wildfire burn severity and biomass burning-induced emissions in California - Qingqing Xu; Anthony LeRoy Westerling; W Jonathan Baldwin (Environmental Research Letters, 2022)
Wildfires are an important disturbance in the Earth system, and their emissions have regional and even global impacts on radiation, clouds, and climate. The increased frequency and magnitude of California wildfires in recent years is altering the terrestrial carbon cycle, undermining the state’s efforts to reduce the Greenhouse Gases (GHGs) to confront climate change. Air quality and public health are also greatly affected by air pollution from wildfires. The severity of wildfire burns is a critical indicator of both their direct and indirect ecological and human impacts. To formulate targeted mitigation strategies, it is imperative to understand the evolving scale, location and timing of wildfire burn severity and emissions. This study analyzed spatial and temporal patterns of burn severity and emissions at 30 m resolution from large wildfires (>404 hectares) burning in California during 1984–2020 from the recently developed Wildfire Burn Severity and Emissions Inventory. Results show vegetation and severity play critical roles in controlling the spatial and seasonal distribution of emissions. California’s annual burned area and emissions increased, notably in early and late parts of what once was the typical fire season, although peak wildfire burned area and emissions continue to occur in mid-Summer. Emissions and areas burned in moderate to high severity were particularly high and increasing in North Coast and Sierra Nevada forests. The 2020 fire year—with the most megafires in California history—had 15 times the annual average emissions that occurred during 1984–2015.